2022
DOI: 10.2174/1871520622666220421092831
|View full text |Cite
|
Sign up to set email alerts
|

Celastrus orbiculatus Extract Inhibits the Invasion and Migration of Human Gastric Cancer Cells in the Hypoxia Microenvironment

Abstract: Background: Gastric cancer is a common global cancer disease. So far, the best choice for diagnosis and treatment of gastric cancer includes surgical resection, chemotherapy, and other targeted drug therapies, however, the overall survival rate of gastric cancer patients is still very low. Hypoxic microenvironment facilitates tumor cells to develop tolerance to chemotherapy and radiotherapy, and promotes the early invasion and metastasis of various tumors. Celastrus Orbiculatus extract (COE) has shown inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The extraction and use of the effective components of COE have been authorized by the national invention patent (Grant No: 200710025343.3). The previous research results showed that COE could inhibit EMT, invasion, and the metastasis of GC cells [15][16][17][18]. However, the main anti-GC components of COE are still being explored.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction and use of the effective components of COE have been authorized by the national invention patent (Grant No: 200710025343.3). The previous research results showed that COE could inhibit EMT, invasion, and the metastasis of GC cells [15][16][17][18]. However, the main anti-GC components of COE are still being explored.…”
Section: Introductionmentioning
confidence: 99%